Juvenile Idiopathic Arthritis: Essential Elements of Care - Alam, Md Rajibul (Journal of Bangladesh College of Physicians and Surgeons, 2010)
The chronic arthritides in childhood remain a poorly understood group of conditions. Their classification has been a source of much confusion over the years with differences in terminology used by different research groups. Childhood arthritis is an important cause of short term morbidity in children and can lead to long term joint destruction and disability. Proper diagnosis and early aggressive intervention can minimize both the short and long term morbidity of the disease, thereby improving outcome during childhood as well as in adulthood. The various sub-types of JIA with their clinical features, diagnosis and differential diagnosis have been described. An outline of current management strategies and outcome of treatment are given and potential future developments are highlighted. DOI: 10.3329/jbcps.v26i2.4186 J Bangladesh Coll Phys Surg 2008; 26:83-90